Radioligand therapies in cancer: mapping the educational landscape in Europe - Bugani, Valentina; Battistelli, Luca; Sansovini, Maddalena; Monti, Manuela; Paganelli, Giovanni; Gich, Ignasi; Flotats, Albert; Erba, Paola Anna; Blay, Jean Yves; la Fougère, Christian; Van Poppel, Hendrik; Charalambous, Andreas; et al. (My University, 2023)
Aim: We performed a systematic survey to assess the existing gaps in Europe in multidisciplinary education for integration of radioligand therapy (RLT) into cancer care and to obtain detailed information on the current limitations and key contents relevant. Methods: A high-quality questionnaire, with emphasis on survey scales, formulation, and validity of the different items, was designed. An expert validation process was undertaken. The survey was circulated among medical specialties involved in cancer treatment, universities, and nursing organizations. Questionnaires (156) were distributed, and 95 responses received. Results: Sevety-eight percent of medical societies indicated that training in RLT was very important and 12% important. Eighty-eight percent indicated that their specialty training program included RLT. Twenty-six percent were satisfied with the existing structure of training in RLTs. Ninety-four percent indicated that the existing training is based on theory and hands-on experience. Main identified limitations were lack of centers ready to train and of personnel available for teaching. Sixty-five percent indicated that national programs could be expanded. Fifty percent of consulted universities indicated partial or scarce presence of RLT contents in their teaching programs. In 26% of the cases, the students do not have the chance to visit a RLT facility. A large majority of the universities are interested in further expansion of RLT contents in their curriculums. Nursing organizations almost never (44.4%) or occasionally (33.3%) include RLT contents in the education of nurses and technologists. Hands-on experience is almost never (38%) and sometimes (38%) offered. However, 67% of centers indicated high interest in expanding RLT contents. Conclusion: Centers involved recognize the importance of the training and indicate a need for inclusion of additional clinical content, imaging analysis, and interpretation as well as extended hands-on training. A concerted effort to adapt current programs and a shift towards multidisciplinary training programs is necessary for proper education in RLT in Europe.
Keywords: Radioligand therapy; RLT; Education; Cancer; Survey; Training’s gap